AN INVESTIGATION ON STUDENT-TEACHERS’ ACQUISITION OF NEW KNOWLEDGE DURING TEACHING PRACTICE EXERCISE. A CASE STUDY OF UNIVERSITY OF EMBU. - Nyaga, Milcah (Machakos University, 2019)
Teaching practice gives student -teachers an opportunity to apply theoretical knowledge into practical knowledge. The student- teacher is able to interact with school administration, teachers and learners as well as non- teaching staff. The study investigated student –teachers’ acquisition of new knowledge during teaching practice exercise. A descriptive survey design was employed. The respondents were one hundred and sixty and they were randomly selected from four hundred and ninety five student-teachers. The instruments for data collection were student’s questionnaire, interview schedule and researcher’s observation schedules. The data was analysed through descriptive statistics. The findings revealed that some student-teachers acquired new knowledge on professional ethics in teaching career while other student-teachers acquired new knowledge of interacting with school administration, teachers and learners as well as non-teaching staff. In addition, the study reported that the student- teachers acquired knowledge on how to cope with different personalities while other student- teachers acquired soft skills. Further, the study indicated that some student- teachers acquired knowledge on innovations and improvisation of teaching learning resources while other student-teachers sharpened their knowledge in cocurriculum activities. Therefore, the study recommended that all student-teachers should actively be involved in teaching practice exercise. Further, the study recommended that proper induction for student -teachers proceeding for teaching practice exercise is paramount. Moreover, the schools providing attachment to student -teachers need to provide conducive environment. The findings from this study will help universities and colleges when preparing student -teachers for teaching practice.
Keywords: Student- teachers; Knowledge; Teaching practice; Acquisition; Learners.